Description of Students' Critical Thinking Skills in Integrated PjBL STEM Learning Environmental Change Material - Lail Isro, Abda; Anggraito, Yustinus Ulung; Bintari, Siti Harnina (Journal of Innovative Science Education, 2021)
Critical thinking skills are important skills in the 21st century, therefore their attainment needs to be measured to determine future steps in the learning process so that they can be improved. This study aims to describe the critical thinking skills of students after learning with Project Based Learning (PjBL) integrated Science, Technology, Engineering and Mathematic (STEM). This research was conducted with a mix-method approach and a concurrent triangulation strategy. Data collection uses test essay to measure aspects of critical thinking skills including aspects of elementary clarification, basic support, inference, adavanced clarification, and aspect strategy and tactics. Furthermore, the results were analyzed by descriptive analysis. The results showed that the achievement of each aspect of critical thinking skills showed variations. The aspect of elementary clarification score 71.01 in high category, basic support score 72.54 in high category, the inference score 74.65 in high category, adavanced clarification score 58.49 in moderate category, and the aspect of strategy and tactics scored 82.83 in very high category. These results indicate the average critical thinking skills of students in PjBL STEM learning environmental change material on high category.